Analisis Kualitas Pelayanan Pada Karibia Boutique Hotel Medan - Yolanda Setyawati; Arwin Arwin; Yuliana Yuliana; Williny Williny; Anggia Arif (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
PT Citra Agra Pertiwi or known as Karibia Boutique Hotel Medan is a business engaged in the hospitality sector. Karibia Boutique Hotel is a 4-star hotel in Medan City. Established in November 2012, it is located at the Center Point Complex, Jalan Timor Block J No N I – IV Medan, North Sumatra, 20231. This study takes the theory from Tjiptono & Chandra (2019) and discusses the services at Karibia Boutique Hotel Medan with the aim of knowing the quality of service available at Karibia Boutique Hotel Medan. According to Tjiptono & Chandra (2019) the right indicators to measure service quality are reliability, responsiveness, assurance, empathy, and tangibles. The author uses descriptive qualitative research methods. Sources of data used are primary and secondary data. The data collection technique used by the author is field research (interviews), the sample was selected using accidental sampling technique, and theresults of the interviews were tested by triangulation of sources. The results of this study indicate that the quality of service provided by Karibia Boutique Hotel Medan still needs to improve the quality of service.